2012
DOI: 10.1111/j.1468-3083.2012.04525.x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to topical treatment in psoriasis: a systematic literature review

Abstract: Literature data about topical treatment adherence are heterogeneous and scarce. They confirm the limited topical treatment adherence in psoriasis in real life, much lower than what is reported in randomized controlled trials. Therapeutic education and clear instructions on the use of topical agents are necessary to improve adherence. Studies are needed to identify predictors of limited adherence and to identify interventions improving adherence to topical medications in psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
176
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(187 citation statements)
references
References 42 publications
4
176
2
5
Order By: Relevance
“…Preference data indicate that a greater proportion of patients receiving Cal/BD aerosol foam than Cal/BD gel thought it was more effective, easier to apply and generally preferred it compared with previous topical and systemic therapies. These observations may be important in clinical practice, given that adherence to topical therapy remains a significant issue 9. Previous studies have shown that if patients think a treatment is effective and easy to use they are more likely to be adherent,9, 31 which should lead to better treatment outcomes.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Preference data indicate that a greater proportion of patients receiving Cal/BD aerosol foam than Cal/BD gel thought it was more effective, easier to apply and generally preferred it compared with previous topical and systemic therapies. These observations may be important in clinical practice, given that adherence to topical therapy remains a significant issue 9. Previous studies have shown that if patients think a treatment is effective and easy to use they are more likely to be adherent,9, 31 which should lead to better treatment outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…These observations may be important in clinical practice, given that adherence to topical therapy remains a significant issue 9. Previous studies have shown that if patients think a treatment is effective and easy to use they are more likely to be adherent,9, 31 which should lead to better treatment outcomes. Although further studies are needed, these patient preference data suggest that Cal/BD aerosol foam may address some of the current unmet needs of the psoriasis patient population.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Adherence is influenced by multiple factors, which can be patient, disease or treatment related 10. Treatment‐related reasons include lack of efficacy, excessive time applying the medication and poor cosmetic characteristics 4. The vehicle used can therefore also impact adherence,11 as patients generally prefer a vehicle that is simple to apply, quickly absorbed and not greasy 12.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of two different semisolid formulations that incorporate SD was evaluated. Since the properties of topical formulations have a major impact on patient compliance with treatment (Fouéré, Adjadj, Pawin, 2005;Brown, Rehmus, Kimball, 2006;Devaux et al, 2012), textural and rheological characterization of semisolid formulations were performed. …”
Section: Introductionmentioning
confidence: 99%